C-440T/T-331C polymorphisms in the UGT1A9 gene affect the pharmacokinetics of mycophenolic acid in kidney transplantation. (September 2007) - Baldelli, Sara; Merlini, Simona; Perico, Norberto; Nicastri, Annalisa; Cortinovis, Monica; Gotti, Eliana; Remuzzi, Giuseppe; Cattaneo, Dario
Introduction: The immunosuppressive agent mycophenolic acid (MPA) is metabolized by uridine diphosphate glucuronosyltransferase 1A9 (UGT1A9) to 7- O -glucuronide (MPAG) and excreted by multidrug resistance-associated protein 2 in the bile. By contrast, the production of the acyl MPAG, a minor MPA metabolite, was ascribed to UGT2B7 and UGT1A8. Several polymorphisms in the genes encoding for UGT1A9, UGT2B7 and MRP2 proteins have been described. However, their functional role in vivo on MPA metabolism remains poorly defined.Methods: A total of 40 Caucasian kidney transplant patients, given induction therapies (with Campath- 1 H or the combination basiliximab/rabbit antithymocyte globulin) and on maintenance immunosuppression with cyclosporine in combination with mycophenolate mofetil (MMF) in a steroid-free regimen, were enrolled in the pharmacogenetic study. Patients had clinical and hematochemical evaluations at month 6 after transplantation, as well as complete MPA pharmacokinetic assessment. They were genotyped for SNPs in UGT1A9 C-2152T, T-1887G, C-665T, C-440T, T-331C, T-275A, T98C, for the nonsynonymous C802T SNP in UGT2B7, and for ABCC2 SNPs C-24T and G1249A. The association of these polymorphisms with MPA pharmacokinetic parameters was investigated.Results: Differences in the MPA pharmacokinetic profiles confirmed large interpatient variability of MPA exposure, with AUC0––12 values ranging from 7.9 to 50.1 mg*h/ml. MPA AUC0––12 was significantly associated with the presence of UGT1A9 -440/-331 genotypes (TT/CC: 61.5  ±±  2.7 mg*h/ml/g MMF; TC/CT: 45.4  ±±  14.0 mg*h/ml/g MMF; CC/TT: 40.8  ±±  10.8 mg*h/ml/g MMF; p  =  0.005), whereas MPAG exposure was mainly influenced by renal function. The positive association between MPA AUC and SNPs in position -440/-331 found in kidney transplant patients confirmed previous in vitro findings showing that the abovementioned SNPs had a significant impact on UGT1A9 protein content in the liver. The presence of ABCC2 promoter C-24T and exon  10 G1249A SNPs did not cause any significant variation in MPA and MPAG pharmacokinetic parameters.Conclusion: The study demonstrated a significant impact of C-440T/T-331C SNPs in the promoter region of the UGT1A9 gene on MPA pharmacokinetics in renal allograft recipients.